2021
DOI: 10.1038/s41598-021-97361-w
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin attenuates arterial calcification by downregulating oxidative stress-induced receptor for advanced glycation end products in LDLR knockout mice

Abstract: Diabetes is a complex disease characterized by hyperglycemia, dyslipidemia, and insulin resistance. Plasma advanced glycation end products (AGEs) activated the receptor for advanced glycation end products (RAGE) and the activation of RAGE is implicated to be the pathogenesis of type 2 diabetic mellitus (T2DM) patient vascular complications. Sitagliptin, a dipeptidyl peptidase-4 (DPP4) inhibitor, is a new oral hypoglycemic agent for the treatment of T2DM. However, the beneficial effects on vascular calcificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In addition, S100A12 was identified to be involved in the development of atherosclerosis through the S100A12-CD36 axis, and its expression was upregulated in unstable plaques [ 23 ]. It was also previously reported that tumor necrosis factor alpha (TNF- α )+S100A12 treatment stimulated nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity and the production of hydrogen peroxide (H2O2) in human aortic smooth muscle cells (HASMCs) [ 24 ]. The above evidence suggests that S100A12 plays an essential part in inflammation and oxidative stress in numerous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, S100A12 was identified to be involved in the development of atherosclerosis through the S100A12-CD36 axis, and its expression was upregulated in unstable plaques [ 23 ]. It was also previously reported that tumor necrosis factor alpha (TNF- α )+S100A12 treatment stimulated nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity and the production of hydrogen peroxide (H2O2) in human aortic smooth muscle cells (HASMCs) [ 24 ]. The above evidence suggests that S100A12 plays an essential part in inflammation and oxidative stress in numerous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Saxagliptin reduced CD40 expression in inflammatory monocytes and macrophages implicated in the initiation of atherosclerosis [ 11 ]. Sitagliptin is also reported to decrease vascular calcification [ 37 ]. Lin et al reported that sitagliptin also prevents the initiation of arterial calcification by inhibiting the activation of NADPH oxidase and NF-κB, which is followed by a decrease in receptors for advanced glycation end products (RAGE) expression [ 37 ].…”
Section: Cd26 Inhibitors In Diabetic Cardiovascular Diseasementioning
confidence: 99%
“…Sitagliptin is also reported to decrease vascular calcification [ 37 ]. Lin et al reported that sitagliptin also prevents the initiation of arterial calcification by inhibiting the activation of NADPH oxidase and NF-κB, which is followed by a decrease in receptors for advanced glycation end products (RAGE) expression [ 37 ]. There is evidence suggesting sitagliptin stimulates the adenosine monophosphate-activated protein kinase (AMPK) pathway and inhibits the mitogen-activated protein kinase (MAPK) pathway, both of which are implicated in inflammation and atherosclerosis [ 12 ].…”
Section: Cd26 Inhibitors In Diabetic Cardiovascular Diseasementioning
confidence: 99%
“…These included treatment with NO donors application (DETA-NONOate) [ 184 ], sodium nitroprusside (SNP) [ 185 ], NO precursor L-arginine [ 186 ], and co-treatment with BH4, which mitigates eNOS uncoupling, showing modest results in attenuating osteogenic differentiation and endothelial dysfunction [ 15 , 187 , 188 ]. Consecrated therapies, such as angiotensin-converting enzyme (ACE) inhibitors [ 96 ], nebivolol [ 45 ], inhibitors of dipeptidyl peptidase 4 (DPP4), such as sitagliptin and anagliptin [ 89 , 122 , 189 , 190 ], and empagliflozin, a sodium–glucose cotransporter-2 (SGLT2) inhibitor [ 25 ], also interfere and prevent eNOS uncoupling and suppress superoxide production. Currently, there are no RCTs testing the aforementioned theories, lending credence that NO bioavailability modulators might be a cutting-edge therapy in CAVD in the future.…”
Section: Therapeutic Targets Of Oxidative Stressmentioning
confidence: 99%